Change of the driver's functional state by depended on the conditions of his work (Transport systems and technologies, 2019)
Every year the development of the industrial and tourism fields oh the countries industries is increasing. Accordingly, there is a need to increase the level of passenger service`s quality. At the same time, one of the important indicators is the creation of safe driving conditions. It`s necessary to bear in mind that a large number of such transportations is carried out by buses. Therefore, the task is to ensure the driver's reliable and trouble-free operation.It is known that the safety of all road users depends on the reliability of the driver's work. At the same time, the driver is one of the least studied links of the system «driver – car – road – environment". So, the task is to study the psychophysiological indicators of the driver, which represent the reliability of his work. Also, they should show the influence of the environment on the driver`s organism. It should be noted the fact that during work, the driver of the vehicle may be exposed to various external factors. It can affect the driver: being over-stressed, neglecting traffic rules, making erroneous decisions, losing control of the transport process, etc. Such processes can lead to accidents. Accordingly to this, the importance of this kind`s transport research is confirmed.a
Keywords: the driver, functional state, working conditions, strain index